The Potential of Antibacterial and Antioxidant Activities of Oolong Tea Residues - AHMAD NASIR, NOR ATIKAH HUSNA; Sulaiman, Mohamad Yusazmeen; Roslani, Muhammad Akmal; Rahim, Nur Syafiqah; Shuhaime, Norlin; Razali, Zainab; Abd Aziz, Aziyah (International Journal of Engineering and Technology, 2018)
Traditionally, the residues of the Oolong tea were believed to help in reducing beriberi symptoms. However, these residues are often dis-carded without optimizing its potential. Thus, the aim of this study is to screen the potential of Oolong tea residues in terms of their antibacterial and antioxidants properties by using the microdilution method and DPPH (1,1-(diphenyl-2-picrylhydrazyl) Scavenging Activity method. In this study, the tea residues were tested up to five cycles of usage. The antibacterial properties of the residues were tested against several Gram positive and negative bacteria. Results showed the highest percentage of inhibition was observed in S. faecalis (50.8 ± 1.3%), B. subtilis (49.0 ± 2.3%), S. typhimurium (48.8 ± 1.5%), S. aureus (47.8 ± 2.1%), E. coli (43.5 ± 3.6%) and P. vulgaris (35.0 ± 4.0%). The first cycle of the tea residues showed highest percentage of inhibition in all bacteria tested but the antibacterial properties showed significant decrease as the cycle increases. For the antioxidant activities, the colour changed from purple to yellow after the fifth residue cycle suggests the presence of secondary compound such as flavonoid. The first cycle of the Oolong tea residues displayed 56.0% DPPH inhibition at 10 g/ml and 85.9% inhibition at 50 g/ml. Yet, the antioxidants activity of the Oolong tea residues decreased with the increase of the residue cycle. This indicates the effectiveness of Oolong tea residues decreases after several times of usage.